FOOD AT YOUR FINGERTIPS: A REVIEW OF ONLINE FOOD DELIVERY SERVICES - Kamal Baharin, Syaza Nabilah; Fikry, Amily; Abd Aziz, Najdah; Abdul, Azreen Joanna; Shobri, Nor Diyana Mohammed (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This paper reviews the definitions of online food delivery services (OFDs) and customer intention to use them by examining their rapid growth in developed and emerging nations. Digital platforms (websites or mobile applications) that facilitate food ordering and delivery through electronic commerce (e-commerce), with far-reaching implications on food consumption patterns. These services fall under restaurant-to-consumer and platform-to-consumer delivery models. Meanwhile, customer intention to use OFDs implies the influence of price value, convenience, service quality, and user experience on one’s preparedness to use the platforms. The global significance and prevalence of OFDs is irrefutable following the unanticipated emergence of COVID-19. Nevertheless, OFD businesses must strive to accommodate varying consumer needs. These platforms can only be effectively sustained with a sound understanding of the key catalysts for customer purchase intention. From a social perspective, the OFDs have redefined consumers’ dining habits, urban mobility, and community interactions. Such far-reaching implications warrant further examination to maximize the OFD benefits and address potential drawbacks.